Гормональная регуляция половой функции и гистологические особенности яичников в эксперименте при использовании в пищу ГМО-сои - Горбач, Т.В.; Кузьмина, И.Ю.; Губина-Вакулик, Г.И.; Колоусова, Н.Г. (Таврический медико-биологический вестник, 2012)
Вивчено гормональні й гістологічні зміни в тканині яєчників пацюків при тривалому введенні у їжу ГМО. Введення в їжу протягом 6 місяців ГМО-сої практично здоровим пацюкам Вістар приводить до прискорення старіння яєчників. Hormonal and histological changes in a tissue of ovaries of rats are studied at long introduction in nutrition GMO. Introduction in nutrition within 6 months of the GMO-soya to practically healthy rats Vistar leads to an acceleration of ageing of ovaries.